Synchronous Framework Extended for Complex Intersections - Reddy, Radha (2021)
Intelligent intersection management systems are an integral part of Smart Cities and have a profound impact in urban traffic management. I n a previous work, the authors proposed a specific Intelligent Intersection Management Architecture (IIMA) with the associated Synchronous Intersection Management Protocol (SIMP) for simple single-lane isolated intersections that outperformed other competing protocols in throughput, time loss and polluting emissions. IIMA/SIMP supports both autonomous and human-driven vehicles. This paper extends such work to more complex multi-lane intersections, comparing against traditional and intelligent intersection management approaches. Simulation results achieved with SUMO confirm the advantages of IIMA/SIMP even in complex intersections, improving throughput, average speed, waiting time, trip time loss, and associated fuel consumption.obs: Extended Abstract has been accepted and invited for full-paper submission.